The Accuracy and the Acceptability of Ten Popular Indonesian Songs Translation from Indonesian into English - Kumandang Kidung Puja Pamarta (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Songs are short piece of music with word that are sung (Cambridge Dictionary) or in Bahasa Indonesia we can call it "Nyanyian" or "Lagu". A Million of Indonesia's good songs still need to be explored because they are worth being known by more Indonesians and also people from all around the world. In this paper, I collected, translated, and analyzed the ten Indonesian Pop Songs. The analysis of the translation is important to help me as the translator of those songs, to be better by assessing it and it could be an example for others to do this good little movement. The purpose of the study is first, to analyze the Accuracy of the ten songs translation and also to analyze the Acceptability of the ten songs translation.In this study, my songs translation shows the level of Accuracy and Acceptability aspect which are connected with the theory I used in this paper. I used the theory from Mona Baker's (2018), Equivalence at Word Level. There are two main types of meaning in words and utterances that I used; Propositional Meaning for the Accuracy analysis and Expressive Meaning for the Acceptability analysis.